2021
DOI: 10.1007/s11240-021-02149-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of medium composition, genotype and age of explant on the regeneration of hexaploid plants from endosperm culture of tetraploid kiwiberry (Actinidia arguta)

Abstract: Endosperm, an ephemeral and storage tissue, serves as a source of nutrition and protection during embryo development and germination. It can be used for the cultivation of polyploid plants in vitro. Here, results of plant regeneration and acclimatization from the endosperm-derived calli of four cultivars of Actinidia arguta has been presented. Seeds excised from fresh fruit and dry seeds stored for one year served as the sources of endosperm explants of selected tetraploid cultivars of A. arguta. Callus Induct… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 63 publications
0
9
0
Order By: Relevance
“…Plant Growth Regulators (PGRs) are vital organic compounds synthesized by plants, which play an essential role in their differentiation and development at low concentrations [ 23 , 24 ]. The addition of suitable PGRs to the culture media has been effective in regenerating kiwiberry shoots [ 25 ]. It is widely accepted that their addition is required for successful shoot initiation and subsequent proliferation [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Plant Growth Regulators (PGRs) are vital organic compounds synthesized by plants, which play an essential role in their differentiation and development at low concentrations [ 23 , 24 ]. The addition of suitable PGRs to the culture media has been effective in regenerating kiwiberry shoots [ 25 ]. It is widely accepted that their addition is required for successful shoot initiation and subsequent proliferation [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our previous observations (Abdullah et al, 2021) showed that isolated endosperm in kiwiberry cv. Bingo cultured on NOCIM and supplemented with 2,4-dichlorophenoxy-acetic acid (2,4-D) and kinetin resulted in callus induction with cell proliferation only, with no organogenic events like adventitious shoot or root formation, even aer six months of culturing.…”
Section: Introductionmentioning
confidence: 94%
“…In addition, there is no evidence that the fate of endosperm changes under natural conditions. Regardless, we have established a protocol for callus proliferation and shoot induction in the isolated endosperm of the kiwiberry, Actinidia arguta (Abdullah et al, 2021;Popielarska-Konieczna et al, 2020), which is a breakthrough result in terms of dealing with recalcitrant (to dedifferentiation) tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, its edible and distinctive avor fruit has high content of vitamin C, abundant nutritious substances and medicinal usage, and was considered as one of the most nutritious fruits [5][6][7]. For its edible peel, the bright fruit color, the majority of consumers love this fruit, people are aware of the health bene ts associated with consuming A. arguta [8,9]. And it also has many horticultural advantages over the common A. arguta, due to high frost resistance [10].…”
Section: Introductionmentioning
confidence: 99%